Youth multi-sport events in Austria: tourism strategy or just a coincidence?. Issue 3 (3rd July 2017) - Schnitzer, Martin; Schlemmer, Philipp; Kristiansen, Elsa
ABSTRACT: Impact and legacy research of touristic issues has become more popular with the appearance of manifold approaches to examining tourism. In recent years, the region of Western Austria has successfully staged multi-sport youth events, with two being staged in Innsbruck, Tyrol (YOG 2012; ICG 2016) and one in the region of Montafon, Vorarlberg (EYOF, 2015). This leads to the assumption that the high frequency of youth sports events in these regions necessitates and therefore also follows a set hosting policy or at least a strategic approach to event bidding and staging. To examine these assumptions, a mix of desk research and qualitative interviews was chosen, encompassing bidding files, final reports, official tourism statistics, press releases from tourism boards, political working papers, internal documents and interviews with organising committee members, event experts and political representatives. Staging youth sports events is found to have left legacies in Western Austria such as generating immediate overnight stays in the low season and creating a positive image for the host regions, depending on the frequency with which events are staged and affirming the purpose of using events to boost tourism. The host areas lacked a written (youth sport) strategy and unexpectedly, the existing strategies do not include the youth sports events. However, it can be assumed in the case of Innsbruck that a hidden event strategy exists. In conclusion, the study reveals the importance of sharing events and their benefits among the various local stakeholders, thus branding the region as a host city.